Organization of the human fetal subpallium - Pauly, Marie-Christin; Döbrössy, Màté; Nikkhah, Guido; Winkler, Christian; Piroth, Tobias (Frontiers in Neuroanatomy, 2014)
The subpallium comprises large parts of the basal ganglia including striatum and globus pallidus. Genes and factors involved in the development of the subpallium have been extensively studied in most vertebrates, including amphibians, birds and rodents. However, our knowledge on patterning of the human subpallium remains insufficient. Using double fluorescent immunohistochemistry, we investigated the protein distribution of transcription factors involved in patterning of the subventricular zone (SVZ) in the human forebrain at late embryonic development. Furthermore, we compared the development of cortical and striatal precursors between human fetal brain and E14 and E16 fetal rat brains. Our results reveal that DLX2 marks SVZ precursors in the entire subpallium. Individual subpallial subdomains can be identified based on co-expression of DLX2 with either PAX6 or NKX2-1. SVZ precursors in the dLGE and POH are characterized by DLX2/PAX6 co-expression, while precursors in the MGE and PO co-express DLX2/NKX2-1. SVZ precursors in the vLGE are DLX2(+)/PAX6(-)/NKX2-1(-). In terms of staging comparisons, the development of the corpus striatum in the human fetal brain during late embryonic stages corresponds well with the development of the striatum observed in E14 fetal rat brains. Our study demonstrates that the pattern underlying the development of the subpallium is highly conserved between rodents and humans and suggests a similar function for these factors in human brain development. Moreover, our data directly influence the application of ganglionic eminence derived human tissue for cell therapeutic approaches in neurodegenerative disorders such as Huntington’s disease (HD).